Redox sensitivity of the MyD88 immune signaling adapter - Stottmeier, Benjamin; Dick, Tobias P. (Free radical biology and medicine, 2016)
The transcription factor nuclear factor-κB (NF-κB) mediates expression of key genes involved in innate immunity and inflammation. NF-κB activation has been repeatedly reported to be modulated by hydrogen peroxide (H2O2). Here, we show that the NF-κB-activating signaling adapter myeloid differentiation primary response gene 88 (MyD88) is highly sensitive to oxidation by H2O2 and may be redox-regulated in its function, thus facilitating an influence of H2O2 on the NF-κB signaling pathway. Upon oxidation, MyD88 forms distinct disulfide-linked conjugates which are reduced by the MyD88-interacting oxidoreductase nucleoredoxin (Nrx). MyD88 cysteine residues functionally modulate MyD88-dependent NF-κB activation, suggesting a link between MyD88 thiol oxidation state and immune signaling.
Gesehen am 19.05.2020